Upaya Menghadapi Segregasi Sosial dan Bidat: Analisis Sosial-Ilmiah Kolose 2:16-23 - Nuban, Sola Gracia Willcory Melina; Surbakti, Pelita Hati (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2024)
Colossians 2:16-23 is often used as a reference to identify heresies in Colossae. This identification was later assessed as part of Paul's strategy so that the Colossian church could finally face the heresy. So, is the problem of heresy the only problem in the congregation? Unfortunately, a number of interpreters tend to pay less attention to the other social issue. This article wants to show that the idea of the unity of the church, as a body, and Christ, as its head, in this text (v. 19) also indicates the existence of social segregation that was hitting the Colossian church. To prove the above hypothesis, the authors conducted qualitative research with data collection through literature studies. The hermeneutic theory used to interpret the Colossians is Social Scientific Criticism. As a result, it appears that the "group" traditions that were so prominent and strong in Mediterranean society at that time were proven to have resulted in social segregation. That is why v. 19 eventually emerged and became part of the strategy to deal with the problems at Colossae, including the social segregation.